Work in graphic designer home office setting: advantages and disadvantages in view of the professional - Motim, Viviane (2014)
This article analyzed the work of graphic designer home office, investigating, through literature and field research, the advantages and disadvantages perceived by the professional as well as outline some trends. The research followed a qualitative approach and the literature review undertaken a semi-systematic search in database of journals and theses, followed by a questionnaire in the form of survey. The analysis allowed to profile the graphic designer who works in home office and point telecommuting as a trend in this area, as well as identified the reasons why the graphic designer to work at home.